2020
DOI: 10.1093/mnras/staa2448
|View full text |Cite
|
Sign up to set email alerts
|

Insight-HXMT observations of Swift J0243.6+6124: the evolution of RMS pulse fractions at super-Eddington luminosity

Abstract: Based on Insight-HXMT data, we report on the pulse fraction evolution during the 2017-2018 outburst of the newly discovered first Galactic ultraluminous X-ray source (ULX) Swift J0243.6+6124. The pulse fractions of 19 observation pairs selected in the rising and fading phases with similar luminosity are investigated. The results show a general trend of the pulse fraction increasing with luminosity and energy at super-critical luminosity. However, the relative strength of the pulsation between each pair evolves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…rising phase, even though the accretion rate is the same in both cases. This might be related to the hysteresis effects of spectral and temporal properties reported by other authors (e.g., Doroshenko et al 2017;Wang et al 2020;Kong et al 2021). The physical mechanism is still poorly known.…”
mentioning
confidence: 88%
“…rising phase, even though the accretion rate is the same in both cases. This might be related to the hysteresis effects of spectral and temporal properties reported by other authors (e.g., Doroshenko et al 2017;Wang et al 2020;Kong et al 2021). The physical mechanism is still poorly known.…”
mentioning
confidence: 88%
“…We use the rms pulse fraction to quantify the pulse profile. The rms pulse fraction is defined as follows (Wilson-Hodge et al 2018;Wang et al 2020):…”
Section: Energy-luminosity Dependence Of the Pulsed Fractionmentioning
confidence: 99%
“…The pulsed fraction is ∼ 30%. The dependence of PF on the energy of photons may be found in Tao et al (2019) or Wang et al (2020). Note that as we did not do phase-connection between individual observations, Fig.…”
Section: Timing Analysismentioning
confidence: 86%
“…Insight-HXMT provided broadband X-ray data with high cadence (Zhang et al 2019;Kong et al 2020;Wang et al 2020). Using these data Doroshenko et al (2020) reported specific changes in timing and spectral properties of the pulsar.…”
Section: Introductionmentioning
confidence: 99%